Implementation of Islamic Religious Education in Shaping Adolescent Morals - Lilik Khotimatul Ahdziyah; Ihsan Mustofa; M. Sayyidul Abrori (Assyfa Journal of Islamic Studies, 2025)
This study examines the implementation of Islamic Religious Education (IRE) in shaping adolescent morals in Sukatani Village, Kalianda District, South Lampung Regency. The research is motivated by the declining quality of adolescent morals amid rapid globalization and technological advancement, even in rural areas. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation. Subjects included religious leaders, educators, parents, and adolescents. Data analysis followed Miles and Huberman's interactive model: reduction, display, and verification. Results indicate that IRE implementation occurs through formal and non-formal channels, including school learning, TPA activities, youth religious gatherings, and family roles. This implementation positively impacts moral formation, evidenced by increased worship awareness, politeness, and improved social interaction. Supporting factors include a religious community environment, the role of religious leaders, and community religious activities. Inhibiting factors include limited parental involvement, negative social media influence, and weak inter-institutional coordination. The study concludes that IRE plays a vital role in adolescent moral formation, yet stronger synergy between schools, families, and communities is essential for optimal outcomes.